IDENTIFIKASI PERMASALAHAN PEMBELAJARAN MAHASISWA PENDIDIKAN MATEMATIKA PADA MATA KULIAH PROGRAM LINEAR: STUDI KASUS PADA PROGRAM STUDI PENDIDIKAN MATEMATIKA - Lalu Saparwadi; Qurratul Aini (Universitas Islam Negeri (UIN) Mataram, 2016)
The recent study identifies student learning problem on the course of linear program for students at mathematics department. The population is taken from students of mathematics department in Lombok West Nusa Tenggara. The findings show that there are four types of problem faced by students when learning Linear Program, such as: a) the lack number of references relating to the course, b) difficulties in modeling problem to mathematics model, c) teaching strategies causes student difficulties in in modeling problem to mathematics model, and d) students have no idea yet relating to the application of the course.